Geometric tracking control of a quadcopter tiltrotor UAV. Issue 1 (July 2017) - Invernizzi, Davide; Lovera, Marco
Abstract: In this paper the modeling and control law design for a quadcopter tiltorotor UAV are considered. The problem is developed in a geometric setting to obtain an intrinsic control law which achieves local exponential stability for trajectory tracking on SE(3). Starting from a multi-body system, a simplified model for control design is derived, which allows to handle the actuation constraints in a simpler way. Numerical results are provided to show the enhanced capabilities of the tiltrotor platform with respect to the co-planar rotors configuration and to assess the effectiveness of the control law.